2019
DOI: 10.1080/08856257.2019.1708641
|View full text |Cite
|
Sign up to set email alerts
|

Shopping for schools: parents of students with disabilities in the education marketplace in Stockholm

Abstract: This article examines the experiences of parents of students with disabilities when they shop for schools in Stockholm. It looks at the motivations behind school choice, the kinds and sources of information used and the constraints that parents encounter in the school choice process. The results, based on interviews with parents, demonstrate friendship, special support systems and school flexibility as reasons for opting for a particular school. Parents seek school-based and consumer satisfaction information, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
8
0
2
Order By: Relevance
“…By contrast, factors like standards of education, examination results and siblings at school were not key factors. This shows a continuity of parental perspectives across two decades and national settings (Jenkinson 1998;Bagley, Woods and Woods, 2001;Byrne 2013;Tah 2020).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…By contrast, factors like standards of education, examination results and siblings at school were not key factors. This shows a continuity of parental perspectives across two decades and national settings (Jenkinson 1998;Bagley, Woods and Woods, 2001;Byrne 2013;Tah 2020).…”
Section: Discussionmentioning
confidence: 83%
“…More recent Australian research on parental reasons to transfer from mainstream to special schools found these key reasons: child missing out on specialist teaching and resources, the difficulty of the work, lack of teacher aids, the need to provide input as a parent and missing out on learning life skills (Mann, Cuskelly, and Moni 2018). A small-scale Swedish study has also shown that parents of children with disabilities opt for a particular school (mainstream or special) based on their support systems, school flexibility and friendships for their child, while seeking information about the satisfaction of the school (Tah 2020). Parents also reported a lack of choice, inadequate information and support.…”
Section: Previous Research On Parental Choice and Experiencesmentioning
confidence: 99%
“…The articulated goals and values in the marketing information such as the goal to create a positive social climate expressed through safety and well-being do have a general appeal to all consumers including consumers in need of special support. Studies examining students in need of special support have found these factors to be important in the school choice decision by parents of students with disabilities (Glenn-Applegate et al, 2016; Tah, 2019). However, regarding academic goals despite being important in education, they may not necessarily appeal to consumers in need of special support when they choose schools.…”
Section: Methodsmentioning
confidence: 99%
“…However, regarding academic goals despite being important in education, they may not necessarily appeal to consumers in need of special support when they choose schools. A study by Tah (2019) demonstrates that academic considerations do not seem to play an important role when consumers in need of special support choose schools in the context of the Swedish education. Friendship and special support services were found to be more important.…”
Section: Articulated Goals and Valuesmentioning
confidence: 99%
See 1 more Smart Citation